Investigation of the kinetics and mechanisms of nickel and copper ions adsorption from aqueous solutions by date seed derived biochar. Issue 1 (February 2018) - Mahdi, Zainab; Yu, Qiming Jimmy; El Hanandeh, Ali
Highlights: Date seed biochars adsorption capacity Cu 2+ and Ni 2+ were investigated. Biochar with particle size 0.6-1.4 mm and prepared at 550 °C and 3 h was best. Ion exchange mechanism accounted for 70% of the ion removal. Cu 2+ and Ni 2+ adsorption was spontaneous an endothermic process. Abstract: This paper reports on Ni 2+ and Cu 2+ adsorption kinetics and mechanisms by date-seed derived biochar. Biochar was prepared at different temperatures (350–550 °C), heating times (1–3 h) and particle sizes (<0.3–>2.0 mm). Biochar prepared at 550 °C and 3 h heating time with particle size range of 0.6-1.4 mm had the highest adsorption capacity for both ions. Further batch experiments revealed that optimal adsorption occurred around pH 6 with maximum adsorption capacity of 0.421 and 0.333 mmol g −1 for Cu 2+ and Ni 2+, respectively. The experimental data were best fit by the Sips isotherm model and the pseudo-second order kinetics models. Ion exchange mechanism accounted for more than two thirds of the ions removal. Complexation with carboxyl and hydroxyl groups also played significant role in ion removal. Column experiments showed that the effluent pH fluctuated overtime buffering to level slightly above 6 which may have facilitated surface precipitation and resulted in the apparent increase in adsorption capacity. The breakthrough curve obtained in the column experiment was reasonably fit by the Adam-Bohart model. Date-seed derived biochar is a promising material for adsorption for heavy metals from aqueous solutions.